Binary TiO2/reduced graphene oxide nanocomposite for improving methylene blue photodegradation. Issue 3 (20th June 2021) - Trinh, Dinh Ngoc; Viet, Thieu Quang Quoc; Nhu, Tran Huynh; Dat, Nguyen Minh; Thinh, Doan Ba; Hai, Nguyen Duy; Tai, Le Tan; Oanh, Doan Thi Yen; Khoi, Vu Hoang; Nam, Hoang Minh; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: Herein, TiO2 /reduced graphene oxide (TiO2 /rGO) nanocomposites were fabricated using the hydrothermal method and investigated with the amount of titanium precursors. The binary nanocomposites were characterized by modern analysis method. The adsorption capacity and photocatalyst degradation were performed based on methylene blue. The appropriate as‐prepared material with 1.5 mL TIP contained a large specific surface area (110.549 m 2 /g) with TiO2 ranging 4‐25 nm homogenously grafting on the rGO surface. The adsorption results were shown in good accordance with the pseudo‐second‐order while the photoreaction kinetics pursued the pseudo‐first‐order with a high‐rate constant. After the adsorption state, the yield reaches 62.1 % and under UV light for 90 min, 96.8 % of MB was efficiently degraded from water media, which showed a more impressive effect as compared with P25 and rGO. Therefore, the use of TiO2 /rGO could be applied in the mass‐scale treatment of organic pollutants in wastewater.